Optimizing the role of implementers to increase Indonesian sports performance at the international level - Siregar, M. A.; Prayitno, I. H.; Suganda, A. (Proceedings of the 3rd International Conference on Indonesian Legal Studies, ICILS 2020, 1 Jul 2020, Semarang, Indonesia, 2021)
In accordance with Indonesian Act No. 3 of 2005 concerning the National Sports System, the scope of sport includes educational sports activities, recreational sports, and performance sports. Achievement sports are carried out through a process of coaching and developing in a planned, tiered, and sustainable manner with the support of sports science and technology. Achievement sports activities as the spearhead are carried out by their respective sports branches supported by the Government in accordance with the National Sports System law as a regulator, facilitator and implementer of these activities. The Government as the executive power holder should still limit its role as regulator and facilitator. While the role of executor should be carried out by an institution known as the Indonesian National Sports Committee (KONI), which carries out in the sense of organizing sports activities in accordance with the regulations outlined by the Government with all its support including its facilities. In order to achieve a proud achievement at the International level for this reason, it is necessary to revise the current National Sports System law.